Generalized Peritonitis due to Multiple Perforation and Necrotic of Ileum : a Case Report - Rifqyan, Anizar; Tinelo, Ineza Fadia; Bellynda, Wynne; Islami, Ananda Aliza Nurul; Hertanto, Annisa Citra Herrastri (Faculty of Medicine, Universitas Jember, 2024)
Peritonitis is a life-threatening condition with a mortality rate according to WHO of 5.9 million per year. We report the case of an elderly man who complained of severe pain in the entire abdominal region and the results of a plain abdominal radiograph showed peritonitis and obstructive ileus. Exploratory laparotomy and ileal resection were performed, and multiple ileal perforations, 120 cm of necrotic ileum and grade IV adhesions were found. There was post-surgical complications of sepsis and the patient died on the seventh post-operative day. Histopathological examination shows images that was not contributory to the diagnosis. There were no features of malignancy or tendency to a specific infection. Non-specific small bowel perforation can be considered as the etiology of peritonitis because there are no specific pathopneumonic characteristics. Diagnostic and management of surgical emergencies plays a very important role in patient prognosis. Keywords: generalized peritonitis;small bowel perforation;obstructive ileus.